Mental Health Parity and Beyond: Aligning the Public and Private Systems of Care for People with Mental Illness - Purington, Kitty (Maine Policy Review, 2004)
Maine is one of the first states to mandate comprehensive mental health coverage for its citizens under private insurance plans. Mental health advocates nationwide long have lobbied for such parity. In this article, Kitty Purington first provides an overview of the federal and state legislation leading up to the present law. She then compares current parity provisions under private plans with those of MaineCare (Maine’s Medicaid program, reporting that coverage under MaineCare for individuals with serious mental illness still exceeds that which is mandated under private plans. She discusses